2016
DOI: 10.1039/c6sm00582a
|View full text |Cite
|
Sign up to set email alerts
|

AFM mapping of the elastic properties of brain tissue reveals kPa μm−1gradients of rigidity

Abstract: It is now well established that the mechanical environment of the cells in tissues deeply impacts cellular fate, including life cycle, differentiation and tumor progression. Designs of biomaterials already include the control of mechanical parameters, and in general, their main focus is to control the rheological properties of the biomaterials at a macroscopic scale. However, recent studies have demonstrated that cells can stress their environment below the micron scale, and therefore could possibly respond to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 53 publications
3
63
1
Order By: Relevance
“…; Gefen & Margulies, ; Bouchonville et al. ), therefore the baseline value of 150 MPa was altered within the range from 1 to 1500 MPa; (iii) suture properties: our previous experimental measurements (Moazen et al. ) showed a large standard deviation for the suture properties, therefore the baseline value of 30 MPa was varied between 3 and 300 MPa.…”
Section: Methodsmentioning
confidence: 93%
See 2 more Smart Citations
“…; Gefen & Margulies, ; Bouchonville et al. ), therefore the baseline value of 150 MPa was altered within the range from 1 to 1500 MPa; (iii) suture properties: our previous experimental measurements (Moazen et al. ) showed a large standard deviation for the suture properties, therefore the baseline value of 30 MPa was varied between 3 and 300 MPa.…”
Section: Methodsmentioning
confidence: 93%
“…The elastic modulus of the brain is reported to be in the range of 1–30 kPa (Bouchonville et al. ). This is three to four orders of magnitude lower than the baseline value of 150 MPa used in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies shed light on the role of substrate stiffness in axonal extension, growth pattern and branching in vitro [Balgude et al, 2001;Flanagan et al, 2002;Jiang et al, 2010;Koch et al, 2012;Lantoine et al, 2016]. In vivo, neurons encounter environments with heterogeneous rigidities [Elkin et al, 2010;Franze et al, 2011;Iwashita et al, 2014;Bouchonville et al, 2016] which likely act as cues instructing axon navigation. Indeed, a recent work reported that axon pathfinding is influenced by the stiffness of the environment ex vivo and in vivo, in the optic pathway of Xenopus embryos ( Figure 1c) [Koser et al, 2016].…”
Section: Axon Guidancementioning
confidence: 99%
“…Using an advanced atomic force microscopy mapping technique, Bouchonville et al revealed that brain tissue rigidity changes as steeply as 12 kPa/μm. [6] While the mean elasticity of the human-derived pituitary gland tissue was 9.5 kPa, areas with moduli as high as 25.9 kPa and as low as 3.5 kPa were detected. Organs and tissues also receive and interpret a range of biochemical signals that vary in space and time; presentation and removal of biologically relevant molecules affect cell differentiation and morphology.…”
Section: Introductionmentioning
confidence: 99%